Patient-Led Research Collaborative: embedding patients in the Long COVID narrative. (13th April 2021) - McCorkell, Lisa; S. Assaf, Gina; E. Davis, Hannah; Wei, Hannah; Akrami, Athena
Abstract : This article discusses the value of patient-led research, the formation of Patient-Led Research for COVID-19, and how to improve Long COVID care and research. Abstract: A large subset of patients with coronavirus disease 2019 (COVID-19) are experiencing symptoms well beyond the claimed 2-week recovery period for mild cases. These long-term sequelae have come to be known as Long COVID. Originating out of a dedicated online support group, a team of patients formed the Patient-Led Research Collaborative and conducted the first research on Long COVID experience and symptoms. This article discusses the history and value of patient-centric and patient-led research; the formation of Patient-Led Research Collaborative as well as key findings to date; and calls for the following: the acknowledgement of Long COVID as an illness, an accurate estimate of the prevalence of Long COVID, publicly available basic symptom management, care, and research to not be limited to those with positive polymerase chain reaction and antibody tests, and aggressive research and investigation into the pathophysiology of symptoms.